Effect of DA-9701 on Feeding Inhibition Induced by Acute Restraint Stress in Rats - Yong Sung Kim; Moon Young Lee; Jong Seol Park; Eul Sig Choi; Min Seob Kim; Seong Hoon Park; Han-Seung Ryu; Suck Chei Choi (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Background/Aims: Stress has a role in the pathogenesis of functional dyspepsia (FD) and influences food intake in humans and animals. Prokinetic drugs have been used in FD, and some of these drugs reverse the feeding inhibition (FI) induced by acute restraint stress in rats. We aimed to evaluate the effect of DA-9701 on FI induced by acute restraint in rats. Materials and Methods: Male Sprague-Dawley rats were divided into 6 groups: Control (no stress), Stress+vehicle, and Stress+DA-9701 at doses of 1, 3, 10, and 30 mg/kg (n=6∼7). DA-9701 or vehicle was administered through gastric gavage 45 minutes before stress. After 60 minutes of stress, pre-weighed chow was given and the weight of remaining food was measured 30 and 60 minutes later. The effect of DA-9701 on FI was compared after pretreatment with WAY100635, a 5HT1A antagonist. Results: The restraint stress group had significantly less food intake than the control group. After feeding, rats given 1 and 3 mg/kg of DA-9701 showed increased food intake at 60 minutes, but this was not statistically significant. Rats given 10 mg/kg of DA-9701 showed significantly increased food intake at 30 minutes and 60 minutes (P＜0.05). Interestingly, rats given 30 mg/kg of DA-9701 showed a significant decrease in food intake, similar to that of the vehicle group. The beneficial effect of 10 mg/kg of DA-9701 on FI was abolished by the pretreatment with WAY100635. Conclusions: Acute restraint stress reduced food intake in rats and pretreatment with DA-9701 improved stress-induced FI.